PERBANDINGAN USER EXPERIENCE TIKET TRANSPORTASI PADA APLIKASI AGEN PERJALANAN ONLINE - Gardiany Marissa Rizqi; Arianis Chan; Tetty Herawaty (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2022)
This study examines the user experience of users of online travel agent A and online travel agent B. The population in this study are customers who use the second online travel agent, namely online travel agent A and online travel agent B, who have ordered transportation tickets at least twice. User experience is measured through the sub-variables happiness, engagement, adoption and retention, task success, page views, uptime, latency, seven days active users, earnings. The research was conducted by taking a sample of 100 online travel agent A and online travel agent B users with a population of up to. The method in this research is a comparative descriptive analysis with a quantitative approach. The object of surrogate research is user experience. The data analysis used is the Wilcoxon test, the analysis is used to see how the differences between online travel agent A and online travel agent B are through user experience. The results show that there are differences in the experience of transportation ticket users on mobile apps online travel agent A and online travel agent B, this is because respondents have a higher assessment of the experience of online travel agent A. So the conclusion that can be drawn in this is that there are differences in research on User Experience of transportation tickets on mobile apps users online travel agent A and online travel agent B.Penelitian ini mengkaji tentang user experience pengguna tiket transportasi pada mobile apps online travel agent A dan online travel agent B. Populasi pada penelitian ini adalah pelanggan yang menggunakan kedua online travel agent yaitu online travel agent A dan online travel agent B yang telah memesan tiket transportasi minimal dua kali. Pengalaman pengguna diukur melalui sub-variabel happiness, engagement, adoption and retention, task success, page views, uptime, latency, seven days active users, earnings. Penelitian dilakukan dengan mengambil 100 sampel pengguna online travel agent A dan online travel agent B dengan populasi tak hingga. Metode yang digunakan dalam penelitian ini adalah analisis deskriptif komparatif dengan pendekatan kuantitatif. Objek penelitian pengganti adalah pengalaman pengguna. Analisis data yang digunakan adalah uji Wilcoxon, analisis tersebut digunakan untuk melihat bagaimana perbedaan antara online travel agent A dan online travel agent B melalui user experience. Hasil penelitian menunjukkan bahwa terdapat perbedaan pengalaman pengguna tiket transportasi pada mobile apps online travel agent A dan online travel agent B, hal tersebut dikarenakan responden memiliki penilaian lebih tinggi terhadap user experience online travel agent A. Sehingga kesimpulan yang dapat diambil dalam penelitian ini adalah terdapat perbedaan user experience tiket transportasi pada pengguna mobile apps online travel agent A dan online travel agent B.